Allosteric Optical Control of a Class B G‐Protein‐Coupled Receptor. Issue 19 (5th April 2016) - Broichhagen, Johannes; Johnston, Natalie R.; von Ohlen, Yorrick; Meyer‐Berg, Helena; Jones, Ben J.; Bloom, Stephen R.; Rutter, Guy A.; Trauner, Dirk; Hodson, David J.
Abstract: Allosteric regulation promises to open up new therapeutic avenues by increasing drug specificity at G‐protein‐coupled receptors (GPCRs). However, drug discovery efforts are at present hampered by an inability to precisely control the allosteric site. Herein, we describe the design, synthesis, and testing of PhotoETP, a light‐activated positive allosteric modulator of the glucagon‐like peptide‐1 receptor (GLP‐1R), a class B GPCR involved in the maintenance of glucose homeostasis in humans. PhotoETP potentiates Ca 2+, cAMP, and insulin responses to glucagon‐like peptide‐1 and its metabolites following illumination of cells with blue light. PhotoETP thus provides a blueprint for the production of small‐molecule class B GPCR allosteric photoswitches, and may represent a useful tool for understanding positive cooperativity at the GLP‐1R. Abstract : Blues and twos : An "azologue" of BETP, a ligand‐dependent allosteric activator of the glucagon‐like peptide‐1 receptor, acts as a synthetic photoswitch. This allows the levels of cAMP, Ca 2+, and insulin to be optically controlled in living cells by using blue light.